Analysis of Competency Curriculum Alignment in Web-Based Application Development on the Study Program of PTIK UNS with the Industrial World - Wachid Adi Nugroho; Dwi Maryono; puspanda Hatta (Journal of Informatics and Vocational Education, 2023)
This study aims to: determine the application of the competency field curriculum in web-based application development on the UNS PTIK study program, determine the needs in web-based application development competencies on the industrial world, and determine the alignment between the application of the web-based application development competency curriculum on the UNS PTIK study program and the need for competence in the field of web-based application development on the industrial world.The form of this research is qualitative research with 6 research subjects, 3 lecturers and 3 alumnus. Data collection techniques used are document analysis, interviews, and questionnaires. The validity test technique used is source triangulation. The analysis technique used is a comparative descriptive technique.The results of this study indicate that the alignment of the curriculum in the competency field in web-based application development on the PTIK UNS study program with the industrial world as a whole is appropriate, but there needs to be development in several courses and collaborations by involving industry directly in the preparation of the curriculum in the future and there are still several stages in the process of developing web-based applications in practice in lectures have not been carried out.